Pengembangan LKPD Disertai Hybridization Kit Berbasis Discovery Learning pada Materi Bentuk Molekul dengan Teori Hibridisasi untuk Pembelajaran Siswa Kelas X - Noval Lerian; Erlina Erlina*; Andi Ifriany Harun; Rachmat Saputra; Risya Sasri (Universitas Syiah Kuala, 2022)
Molecular geometry is a subject that many students find difficult to understand. This is because students have to imagine those molecules in order to fully understand the content. To help students understand those concepts, the learning meda that can be seen directly is needed. This study aims to produce students’ worksheet (LKPD) on molecular geometry and a Hy-Kit (Hybridization Kit) based on discovery learning. In addition, the validity and students’ responses also measured towards those LKPD and Hy-Kit. The LKPD was arranged based on discovery learning model and equipped with Hy-Kit. The research method is a research and development using the ADDIE model. The test of the product was carried out twice. These are group tests (limited tests) and field tests. The result of the study that discovery learning-based LKPD and Hy-Kit had a validity level of materials aspect, the level of media aspect and level of bahasa aspect were k=1.00 with very high category. The response of students for the group test and for the field test were k= 0.89 and k=0.90 which means very good/valid/very interested. Both results indicates that the LKPD and Hy-Kit are valid, feasible and ready to use in the learning process